Regional differences in prognostic value of cardiac valve plane displacement in systemic light-chain amyloidosis - Ochs, Marco; Fritz, Thomas; Arenja, Nisha; Riffel, Johannes; André, Florian; Mereles, Derliz; Siepen, Fabian aus dem; Hegenbart, Ute; Schönland, Stefan; Katus, Hugo; Friedrich, Matthias; Buß, Sebastian Johannes (Journal of cardiovascular magnetic resonance, 2017)
To compare the prognostic value of cardiac valve plane displacement (CVPD) on various locations in cardiac light chain (AL) amyloidosis.